Multidimensional factors that influence the turnover intention to practice segregation psychological contract, burnout and job insecurity - Mochamad Soelton; Muhammed Hokroh; Muhammad Sadiq; Made Setini; Eko Tama Putra Saratian; Agus Arijanto; Retno Wulandari (Universitas Mercu Buana, 2021)
Human resources are an important resource that supports organizations in achieving competitive advantage. Therefore, it is important to involve employees to drive the strategic goals of the organization. Media companies in the era of globalization are expected to face increasingly fierce competition. Therefore, the quality of the organization must be considered. This is inseparable from the role of human resources who will be required to carry out their duties and functions properly. This study aims to analyze the effect of psychology contract, job burnout, and job insecurity on employee turnover intention permanent employees. The type of research used is a causal relationship with a quantitative approach. The sample of 66 respondents who are employees of the Gramedia Asri Media. Analysis of the data used is descriptive analysis by analyzing data through the Partial Least Square (PLS) application with the SmartPLS 3.0 program. The results of this study indicate that the variables of psychological contract, job burnout and job insecurity influence the turnover intention permanent employees in Gramedia Asri Media employees.